2018
DOI: 10.3389/fbioe.2017.00084
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Aedes aegypti Expression Datasets: Comparing Virus Infection and Blood-Fed Transcriptomes to Identify Markers of Virus Presence

Abstract: The mosquito Aedes aegypti (L.) is vector of several arboviruses including dengue, yellow fever, chikungunya, and more recently zika. Previous transcriptomic studies have been performed to elucidate altered pathways in response to viral infection. However, the intrinsic coupling between alimentation and infection were unappreciated in these studies. Feeding is required for the initial mosquito contact with the virus and these events are highly dependent. Addressing this relationship, we reinterrogated datasets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Immune activation may be a protective mechanism to combat potential invading microbes after the ingestion of a highly nutritional diet such as blood [57]. Moreover, it has been reported that pathogens present in the blood meal caused an enhanced production of immune effector molecules [55,58]. The interactions between insects and entomopathogenic fungi is complex [31,59].…”
Section: Discussionmentioning
confidence: 99%
“…Immune activation may be a protective mechanism to combat potential invading microbes after the ingestion of a highly nutritional diet such as blood [57]. Moreover, it has been reported that pathogens present in the blood meal caused an enhanced production of immune effector molecules [55,58]. The interactions between insects and entomopathogenic fungi is complex [31,59].…”
Section: Discussionmentioning
confidence: 99%
“…All The heatmap was generated in R via the heatmap.2 function from the gplots package, using the "scale = "row" switch to Z-score standardize the rows [31]. PCA was performed in order to compare and visualize the expression values of all genes to estimate the variance of the global gene expression with the function prcomp a native package in R. The decision trees were employed to validate and identify the minimal gene set that correctly classifies the smokers from nonsmokers from the 22-gene signature [32]. To estimate the decision tree models accuracy, we performed a 10-fold cross validation.…”
Section: Discussionmentioning
confidence: 99%
“…The validation set was used to test the classifier performance. The sensibility and specificity were measured from the confusion matrix and visualized in the receiver-operating characteristic curve (ROC) [32]. Accuracy was evaluated by area under the curve of ROC plot.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of antioxidant response proteins takes place upon the consumption of a blood meal [ 14 , 17 ]. Additionally, a blood meal elicits an immune response in the mosquito; however, it has been observed that if a blood meal is infected with a pathogen, there is an enhanced surge of immune effector molecules [ 18 , 19 , 20 , 21 , 22 , 23 ]. Specifically, there is a tissue-specific regulation of these effector molecules, as seen in mosquito genera such as Anopheles and Aedes [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%